Warta ze współczynnikiem humanistycznym. Kulturotwórcze funkcje spożywania alkoholu na terenach nadrzecznych w Poznaniu - Wechta, Przemysław (Rocznik Pedagogiczny, 2021)
The aim of the article is to apply the concept of the humanistic coefficient of Florian Znaniecki to the analysis of a specific legal and social situation that enabled the legal consumption of alcohol in the Warta areas in Poznan. They have gained a high spatial value, and this is not due to intentional investments or architectural changes, but thanks to the presence of people who create various types of social systems. Znaniecki’s humanistic coefficient turns out to be not only an important theoreti- cal concept, but also a useful, still valid tool in empirical analysis. It brings a large dose of practical knowledge for different types of decision makers (re)organizing urban areas. The spatial value does not have to be directly proportional to the size of financial outlays.